Indeks jurang kemajuan berasaskan entropi dengan fungsi ketumpatan kebarangkalian - Abdul Aziz Jemain; Khairul Anuar Mohd Ali (Penerbit ukm, 2005)
This paper suggests a method to compute weight for each criterion used in constructing a development disparity index. The weights are obtained base on the entropy for each criterion. The entropy value for a criterion was calculated using estimated density function for the data correspond to each criterion. This method is different from those suggested by Hwang & Yoon (1981), and by Chen & He (1997)